2023
DOI: 10.1186/s40168-022-01440-7
|View full text |Cite
|
Sign up to set email alerts
|

The bovine foot skin microbiota is associated with host genotype and the development of infectious digital dermatitis lesions

Abstract: Background Bovine Digital Dermatitis (BDD) is a prevalent infectious disease, causing painful foot skin lesions and lameness in cattle. We describe herein the bovine foot skin microbiota and its associations with BDD using 16S rRNA gene amplicon and shotgun metagenomic sequencing on samples from 259 dairy cows from three UK dairy farms. Results We show evidence of dysbiosis, and differences in taxonomy and functional profiles in the bovine foot ski… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Another potentially mediating variable is the gut microbiome. An effect of the gut microbiome on the immune system [ 41 ], udder [ 42 , 43 ] and claw health [ 44 ] has already been mentioned by several studies. In addition, Monteiro et al [ 45 ] reported an association between the level of milk production and the microbiome of the rumen as well as of the lower gut.…”
Section: Discussionmentioning
confidence: 99%
“…Another potentially mediating variable is the gut microbiome. An effect of the gut microbiome on the immune system [ 41 ], udder [ 42 , 43 ] and claw health [ 44 ] has already been mentioned by several studies. In addition, Monteiro et al [ 45 ] reported an association between the level of milk production and the microbiome of the rumen as well as of the lower gut.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the delayed recovery of sole ulcers is the development of complicating secondary infections with bacteria such as treponemes, which are more frequently associated with bovine digital dermatitis ( Evans et al, 2011 ; Sykora et al, 2015 ). This complication could conceivably have a genetic background because genotype has been associated with the microbiome of chronic wounds in humans ( Tipton et al, 2020 ) and foot skin microbiome in cattle ( Bay et al, 2021 ). Another possible mechanism for genetic influence on sole lesion recovery is via IGF-1, which is a major promoter of wound healing ( Garoufalia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, other novel uncultured Treponema spp. have also been detected within BDD lesions from domestic cattle ( 6 , 11 , 12 ). Collectively, these findings have led to the hypothesis that PT19, and perhaps other novel spirochetes, are likely associated with TAHD in free-ranging elk ( 3 ).…”
Section: Introductionmentioning
confidence: 97%